Pendidikan Kesehatan Yang Service Execellent Tentang Edukasi Pencegahan Anemia Pada Ibu Hamil Masa Pandemi Covid – 19 Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serang Tahun 2023 - Dessy Ratna Sari; Ariska Fauzianty; Friza Novita Sari Situmorang; Lasria Youlivia Aruan; Eka Purnamasari; Diana Viranthy Surbakti (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Pregnant women are prone to anemia, because during pregnancy, especially at the end of pregnancy, the process of hemodilution occurs. This process is due to the increase in blood plasma volume in the body which is not proportional to the increase in red blood cell volume, resulting in a decrease in hemoglobin levels in the blood (Ali, 2020). A decrease in hemoglobin levels during pregnancy will cause a decrease in oxygen transport to the body and result in anemia (Percy, et al., 2017). Anemia during pregnancy has long-term and short-term impacts. In the short term, a fetus with an anemic mother in the first trimester is at risk of small for gestational age (SGA) and fetal distress. In Trimester II, the fetus is at risk for macrosomia (Sun et al., 2021), and in Trimester III in the long term it will have an impact on neurocognitive in childhood. Long-term effects include autism, schizophrenia, brain structural abnormalities, impaired thinking memory, and delays in responding to things (Georgieff, 2020; Malinowski et al., 2021). The impact of anemia on mothers during pregnancy in the short term includes infectious shock during inpartum and postpartum (Getahun, et al., 2017), cardiac decompensation (Stephen et al., 2018), and postpartum hemorrhage (Getahun, et al., 2017). In the long term, postpartum hemorrhage leads to death. Meanwhile, postpartum hemorrhage is the first cause of high maternal mortality rates (MMR) in Indonesia in 2020.